Conspecific sperm precedence is reinforced, but postcopulatory sexual selection weakened, in sympatric populations of Drosophila - Castillo, Dean M. (Proc Biol Sci, 2019)
Sexual selection can accelerate speciation by driving the evolution of reproductive isolation, but forces driving speciation could also reciprocally feedback on sexual selection. This might be particularly important in the context of ‘reinforcement’, where selection acts directly to increase prezygotic barriers to reduce the cost of heterospecific matings. Using assays of sperm competition within and between two sister species, we show a signature of reinforcement where these species interact: populations of Drosophila pseudoobscura that co-occur with sister species D. persimilis have an elevated ability to outcompete heterospecific sperm, consistent with selection for increased postcopulatory isolation. We also find these D. pseudoobscura populations have decreased sperm competitive ability against conspecifics, reducing the opportunity for sexual selection within these populations. Our findings demonstrate that direct selection to increase reproductive isolation against other species can compromise the efficacy of sexual selection within species, a collateral effect of reproductive traits responding to heterospecific interactions.